Ludwig van - Kagel, Mauricio 1931-2008; Feller, Carlos; Pearson, William; Canino, Bruno; Rzewski, Frederic 1938-2021; Gawriloff, Saschko; Ojstersek, Egbert; Ruymen, Gérard; Palm, Siegried (Hamburg Deutsche Grammophon, 1970)
Back cover has an interview with Mauricio Kagel conducted by Karl Faust in German. Comes with LP-sized insert containing the same interview translated into English and French.
Keywords: Beethoven, Ludwig van -- 1770-1827; 20th Century (1901-2000); Chamber music; Avant-garde; Germany